Development of novel self-healing and antibacterial dental composite containing calcium phosphate nanoparticles. Issue 3 (March 2015) - Wu, Junling; Weir, Michael D.; Melo, Mary Anne S.; Xu, Hockin H.K.
Abstract Objectives Fracture and secondary caries are the primary reasons for dental restoration failure. The objective of this study was to develop a self-healing composite to heal cracks, while containing dimethylaminohexadecyl methacrylate (DMAHDM) for antibacterial function and nanoparticles of amorphous calcium phosphate (NACP) for remineralization. Methods Microcapsules were synthesized with poly(urea-formaldehyde) (PUF) shells containing triethylene glycol dimethacrylate (TEGDMA) and N, N-dihydroxyethyl-p-toluidine (DHEPT) as healing liquid. Composite contained 20 mass% of NACP and 35% glass fillers. In addition, composite contained 0%, 2.5%, 5%, 7.5%, or 10% of microcapsules. A single edge V-notched beam method measured fracture toughness (KIC) and self-healing efficiency. A dental plaque microcosm biofilm model was used to test the antibacterial properties. Results Incorporation of microcapsules up to 7.5% into the composite did not adversely affect the mechanical properties (p > 0.1). Successful self-healing was achieved, with KIC recovery of 65–81% (mean ± sd; n = 6) to regain the load-bearing capability after composite fracture. The self-healing DMAHDM-NACP composite displayed a strong antibacterial potency, inhibiting biofilm viability and lactic acid production, and reducing colony-forming units by 3–4 orders of magnitude, compared to control composite without DMAHDM. Conclusions A dental composite was developed with triple benefits of self-healing after fracture, antibacterial activity, and remineralization capability for the first time. Clinical significance The self-healing, antibacterial and remineralizing composite may be promising for tooth cavity restorations to combat bulk fracture and secondary caries. The method of using triple agents (self-healing microcapsules, DMAHDM, and NACP) may have wide applicability to other dental composites, adhesives, sealants and cements.